Management Analysis APBDES Of The Development Level Of Buae Village, Watang Pulu District, Sidenreng Rappang Regency - Anwar Anwar; Irmawati Irmawati (Journal AK-99, 2023)
This study aims to determine the management (APBDes) of the development level of Buae Village. To apply these objectives, a qualitative method is used, using observation and interview techniques. This type of research used is qualitative with descriptive elaboration, namely a research that aims to obtain an overview to understand and explain the use of village APBDes in Buae Buae village, Wattang PuIu sub-district, Sidenreng Rappang district. There are three data collection techniques used including: observation, interviews, and documentation. The results of this study show that in planning the APBDes program in Buae Village, the concept of village community participation development has been implemented as evidenced by the application of the principle of participation. The implementation of the APBDes program at the level of development in Buae Village has not fully implemented the principles of good governance, namely transparency in the field of village financial management. APBDes reporting has been proven by accountability for the implementation of the APBDes program to the government above it. Village government officials can report the budget in accordance with applicable regulations. For the accountability report on the implementation of the APBDes, technically and administratively it is good. Broadly speaking, APBDes management of the village development level has increased from both physical and non-physical development.